2019
DOI: 10.3390/ma12152389
|View full text |Cite
|
Sign up to set email alerts
|

Development of Composite Scaffolds Based on Cerium Doped-Hydroxyapatite and Natural Gums—Biological and Mechanical Properties

Abstract: Hydroxyapatite (HAp) is a ceramic material composing the inorganic portion of bones. Ionic substitutions enhance characteristics of HAp, for example, calcium ions (Ca2+) by cerium ions (Ce3+). The use of HAp is potentialized through biopolymers, cashew gum (CG), and gellan gum (GG), since CG/GG is structuring agents in the modeling of structured biocomposites, scaffolds. Ce-HApCG biocomposite was synthesized using a chemical precipitation method. The obtained material was frozen (–20 °C for 24 h), and then vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…After 48 h, the amount the alive nauplii remained above 50.0%, confirming the non-toxicity of all the samples. As described by the literature, the CG polysaccharide and PAM do not exhibit significant toxicity [ 29 , 83 ]. Acrylamide is a water-soluble substance and has high toxicity [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…After 48 h, the amount the alive nauplii remained above 50.0%, confirming the non-toxicity of all the samples. As described by the literature, the CG polysaccharide and PAM do not exhibit significant toxicity [ 29 , 83 ]. Acrylamide is a water-soluble substance and has high toxicity [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the substitution with cerium ions improves the chemical and biological properties of calcium phosphates but can also have an antibacterial action inhibiting the development of pathogens (Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus and Bacillus subtilis). Several research studies also suggested that cerium ions had a positive effect on the processes of proliferation, differentiation and mineralization of osteoblasts [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the highest level of cell viability and proliferation were observed for GelMA-HC5 composite, in comparison with GelMA-HC1 composite (p < 0.01). Previous studies [10] investigated the effect of doped-hydroxyapatite containing 5% (w/w%) cerium, cashew gum and gellan gum in contact with rabbit mesenchymal stem cells. The results showed that the proposed scaffold supported cell viability and cell growth, that are suitable for bone regeneration applications.…”
mentioning
confidence: 99%
“…Therefore, in order to confer good antimicrobial properties, into the hydroxyapatite structure may be introduced metallic ions, such as zinc, cerium, silver, etc. [8][9][10][11][12]. Among these, zinc ions play an important role in the bone physiology [13] involved in processes such as bone development and DNA replication [7].…”
Section: Introductionmentioning
confidence: 99%